Medical Science in The Qur'anic View - hasanuddin hasanuddin; kaizal bay (Khatulistiwa, 2021)
Al-Quran is, the word of Allah SWT revealed to the Prophet Muhammad through the intermediary of the angel Jibril as., reading it is considered worship, written in one Mushaf, starting from the beginning of the Surah Al-Fatihah to the end of the An-Nas Surah which is mut generations . Inside there are various kinds of knowledge, a set of rules and prohibitions, stories and everything that benefits human life. Medical science is the science that discusses ways of maintaining the human body to stay healthy and able to carry out its functions properly, procedures for overcoming diseases and how to prevent the disease from reappearing. The Koran has regulated this through His verses with a set of rules and prohibitions such as the command to eat halal and healthy food, the order to maintain rest periods, the importance of fasting, the prohibition on eating pork, the prohibition of drinking khamr and various other orders and prohibitions. In addition, the Prophet also taught humans to live a healthy and clean life through a series of his daily sunnah and procedures for the treatment of diseases known as Thibbun Nabawi. This method of Nabawi Nabawi includes in the form of concoctions such as; Black Seed, honey, then in the form of therapy; like cupping, in the form of rukyah; namely by using the verses of the Koran as a remedy for the final and inner diseases.